Establishing acoustical standards within environments for the aging: What should we be building? - Post, Jessica; Kaup, Migette L. (My University, 2008)
Currently one in twenty-five people are at retirement age; in the near future, this figure will jump to one in eight (Weinstein, 2000, p. 10). This demographic curve represents the cohort commonly referred to as “baby-boomers,” who will retire as an influential, active, and expectant body of individuals (Levin, 2002; Peck, 2003; The Growth of America’s Older Population, 2000). Despite anticipating this growing older population, acoustical standards are not being considered in even most award-winning long term care (LTC) facilities, where an estimated one in three residents have some form of hearing impairment (Dugan, 2003, p. 22; Healthcare Design, 2002; Healthcare Design 2003). These unique acoustical issues include understanding hearing within the aging process, application of existing acoustical standards and research to health care facilities, and discussing what should be built to maintain a high quality of life for residents in LTC environments.
Keywords: Gerontology; Acoustical standards; Long-term care facilities